Peran Guru Sebagai Agen Sosial dalam Pembentukan Struktur Sosial Sekolah - Syfa Maulidiyah; Nur Khasanah; Siti Nur Azizah (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
Education plays a crucial role in enhancing intellectual abilities and shaping individuals to become more capable and accomplished. However, the current education system is considered to be too focused on cognitive aspects while neglecting the development of students’ character and moral values, which has led to various social issues. In this regard, the sociology of education emerges as an effort to understand the relationship between education and society, as well as how social, cultural, economic, and historical factors influence the development of students’ character. This study employs a literature review method by examining various written sources such as books, academic journals, and relevant research reports. The findings indicate that the sociology of education plays a significant role in shaping students’ character through the understanding of existing social values, norms, and ethics. Through the theories of functionalism, conflict, and symbolic interactionism, the sociology of education contributes to explaining the role of education in society and how social interactions within the school environment can strengthen the development of positive character. Moreover, teachers as social agents in schools—including principals, homeroom teachers, and special education assistants—have a strategic role in creating an inclusive, adaptive, and character-oriented educational atmosphere. Thus, the sociology of education is not only an academic field but also serves as a tool to shape individuals who are ethical, empathetic, and capable of contributing positively to society.